R-lipoic acid overdosing affects platelet life span via ROS mediated autophagy. (3rd October 2018) - Liu, Jing; Song, Qingqing; Huang, Yanwei; Sun, Wu; Lu, Dingqiang; Zhou, Bo
Abstract: R-lipoic acid (ALA), a powerful antioxidant valuable for the treatment of diabetes and its complications, has been reported to exhibit an antiplatelet activity in vitro. The aim of this study was to investigate the effect and mechanism of ALA on platelets in vivo. Sprague-Dawley (SD) male rats were intravenously administered with low-dose ALA (20 mg/kg/d), high-dose ALA (80 mg/kg/d) and saline, respectively. Platelets count and bone marrow smear were evaluated and the expressions of markers related to apoptosis and autophagy were measured. Platelet clearance analysis was conducted out on mice. The results showed that high-dose ALA administration could significantly decrease platelet count by 43% compared with control group, whereas, megakaryocytes showed no difference in the number. Moreover, high-dose ALA administration led to significant reduction in half-life of circulating platelets, indicative of enhanced rate of platelet clearance. Interesting, high-dose ALA administration could increase the level of reactive oxygen species (ROS) in platelets and induce autophagy without affecting apoptosis. Our finding also showed that high ALA-induced autophagy in platelets was mediated by class III PtdIns3K activity, which could be reversed by 3-methyladenine (3-MA). Moreover, AKT and MAPK/ERK pathways were also observed to be involved in the regulation of autophagy in platelets. Thus, high-dose ALA could induce autophagy in platelets through modulating the activity of class III PtdIns3K, which was associated with decreased count of circulating platelets and shortened lifespan of platelets.